Implementasi Audit Internal Syariah Untuk Mencapaian Good Univercity Governance (GUG) Yang Baik - Fatimah, Dewi; Vena Annisa, Tasya; Djasuli, Mohammad (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2023)
Good University Governance is the governance of educational institutions carried out or carried out by stakeholders who play an active role in educational institutions that have benefits in it, namely increasing the welfare of stakeholders, achieving the best accreditation and being able to be competitive in the current global era. Educational institutions, especially higher education institutions that really need to implement Good University Governance so that these higher institutions produce a positive impact, can make progress and development of the governance of the institution. In achieving Good University GovernanceThis can be done well if the higher institution carries out internal control, namely having an Internal Control Unit (SPI) at universities in Indonesia by using an internal audit unit. The purpose of this research is to be able to determine the application of internal audit based on Islamic or sharia in achieving Good Governance Univercity good . This research uses descriptive qualitative method, namely analyzing data from various sources. The data used is secondary data, namely taking literature obtained from books, archives, reports, journals, and others, both published and unpublished. In addition, it is obtained from the Qur'an and Hadith as well as to find out in Islam based. The application of a very good internal auditor, which is able to use an Islamic perspective or based on honesty, fairness, and trust in the governance of high institutions.